Improved field evaluation of reference cells using spectral measurements. (February 2021) - Vignola, Frank; Peterson, Josh; Kessler, Richard; Sandhu, Vikram; Snider, Sean; Habte, Aron; Gotseff, Peter; Andreas, Afshin; Sengupta, Manajit; Mavromatakis, Fotis
Highlights: Evaluates the performance of a reference cell on a one-axis tracker. Presented a model that uses spectral irradiance data to model the output of the reference cell. A good match was found between the modeled reference cell output and the reference cell measurement. A simplified comparison between reference cell measurements and spectral irradiance measurements is suggested. Suggestions for more through testing of reference cell spectral response is presented. Abstract: Output from an IMT reference solar cell mounted on a one-axis tracking surface is investigated using spectral measurements covering the 350–1650 nm range for selected days throughout the year. Comparisons are made to a Class-A pyranometer also mounted on the one-axis tracking surface. Systematic biases over the day and year are observed in the ratio of the reference cell's measurements to reference pyranometer measurements. This systematic bias is associated with the spectral, temperature, and angle-of-incident effects that differ between the reference cell and the reference pyranometer. The comparison is done for selected clear and totally cloudy days to determine the magnitude of the effects and to characterize the influence of these effects on the reference cell measurements. A model to calculate the reference cell output based on spectral irradiance and reference cell temperature is introduced.